KINERJA KARYAWAN YANG DIDASARKAN PADA BEBAN KERJA, KOMPENSASI, DAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PT. INDAH PERMAI DEPO DENPASAR - Tiksnayana Vipraprastha; Bagus Nyoman Kusuma Putra (Journal of Applied Management Studies, 2023)
The purpose of this research is to find out whether workload, incentives, and organizational citizenship behavior (OCB) have an impact on the performance of PT. Beautiful Permai Depot Denpasar. Samples were collected using the saturated sampling technique with the slovin formula, amounting to 67 respondents. The data analysis technique used in this study is multiple regression analysis. The results showed that: (a) there is a significant and negative effect between workload and employee performance with a coefficient value of -0.878 and a significance value of 0.383 , (b) there is a significant and positive effect between fatigue and employee performance with a coefficient value of 3.605 and a significance value of 0.001, and (c) there is a significant and positive influence between the behavior of organizational members (ocb) and employee performance with a coefficient value of 5.842 and a significance value of 0.000.